Experimental data for solid–liquid flows at intermediate and high Stokes numbers. (25th January 2020) - Mena, Sarah E.; Curtis, Jennifer Sinclair
Abstract : Abstract : Experimental data for turbulent solid–liquid flow in a vertical pipe were collected for glass beads with diameters from 0.5 mm to 5 mm, at concentrations up to 2 % v/v, and Reynolds numbers from 200 000 to 350 000. In addition, data for crushed glass, steel shot and two sizes of stainless-steel cylinders were also collected. The experiments span from the intermediate to the inertia-dominated regimes, and the results include direct measurements for the pressure drops, the solids concentration and the three velocity components for each of the phases using laser Doppler velocimetry and phase Doppler anemometry. In addition, the results include the Reynolds stresses, the granular temperature, the kinetic energy and calculations for the turbulence modulation. The results show augmentation of turbulence for all the conditions studied. The velocity fluctuations for the solid and the liquid are reduced with increasing Reynolds numbers at all conditions. The Reynolds number dictates the behaviour of the relative velocity with concentration: for the Reynolds number of 350 000, the relative velocity increases with increasing concentrations, which can be explained by a decrease in the solid shear and an increase in the solid-phase pressure with rising concentration. In contrast, for the Reynolds number of 200 000, the relative velocity decreases with increasing concentrations, which can be attributed to an increase in drag force at higher concentration. The unique dataset presented begins to close the gap in knowledge for two-phase flow experimentation at concentrations above 0.7 % v/v and Reynolds numbers above 30 000.